Second-generation taxanes effectively suppress subcutaneous rat lymphoma: role of disposition, transport, metabolism, in vitro potency and expression of angiogenesis genes - Otová, Berta; Ojima, Iwao; Václavíková, Radka; Hrdý, Jiří; Ehrlichová, Marie; Souček, Pavel; Vobořilová, Jana; Němcová, Vlasta; Zanardi, Ilaria; Horský, Stanislav; Kovář, Jan; Gut, Ivan (Investigational new drugs, 2012)
The study investigated possible mechanisms by which second-generation taxanes, established as significantly more effective than paclitaxel in vitro, suppress a rat lymphoma model in vivo. The studied mechanisms included taxane pharmacokinetics, expression of genes dominating their metabolism (Cyp3a1/2) and transport (Abcb1) and genes controlling tumour angiogenesis (growth factors and receptors). SB-T-1214, SB-T-12854 and IDN5109 suppressed rat lymphoma more effectively than paclitaxel, SB-T-12851, SB-T-12852, SB-T-12853 or IDN5390 as well as P388D1 leukaemia cells in vitro. The greater anti-lymphoma effects of SB-T-1214 in rats corresponded to a higher bioavailability than with SB-T-12854, and lower systemic toxicity of SB-T-1214 for rats reflected its lower cytotoxicity for P388D1 cells in vitro. Suppression of Abcb1 and CYP3a1 expression by SB-T-1214 and IDN5109 could partly explain their anti-lymphoma effects, but not that of SB-T-12854. Growth factors genes Egf, Fgf, Pdgf, and Vegf associated with tumour angiogenesis had significantly lower expression following treatment with anti-lymphoma effective IDN5109 and their receptors were unaffected, whereas inefficient IDN5390 increased expression of the most important Vegf. The effective SB-T-12854 inhibited Egf, Egfr, Fgfr and Pdgfr expression, while the ineffective SB-T-12851, SB-T-12852 and SB-T-12853 inhibited only Egf or Egfr expression. Vegfr expression was inhibited significantly by SB-T-12851 and SB-T-12854, but effect of SB-T-12851 was compromised by induced Vegf expression. The very effective SB-T-1214 decreased the expression of Vegf, Egf and all receptors most prominently indicating the possible supporting role of these genes in anti-lymphoma effects. In conclusion, SB-T-1214, SB-T-12854 and IDN5109 are good candidates for further study.
Keywords: patologická angiogeneze; regulace genové exprese u nádorů; Animals; Cytochrome P-450 CYP3A; tumor burden; Female; ženské pohlaví; Gene Expression Regulation, Neoplastic; Tumor Burden; lymfom; ATP Binding Cassette Transporter, Subfamily B; protinádorové látky; cytochrom P-450 CYP3A; Antineoplastic Agents; membránové proteiny; Taxoids; Rats, Sprague-Dawley; P-glykoproteiny; Lymphoma; Male; potkani Sprague-Dawley; krysa rodu Rattus; Membrane Proteins; Neovascularization, Pathologic; plocha pod křivkou; zvířata; mužské pohlaví; taxoidy; Rats; Area Under Curve